The Effect of Vitamin D Supplementation on the Increase in CD4 count of HIV/AIDS Patients Receiving Antiretroviral Therapy - Mega Permata; Harun Hudari; Mediarty; Taufik Indrajaya (HM Publisher, 2021)
Introduction. Vitamin D plays a role in health overall, but hypovitaminosis D stilloccurs throughout the world. HIV/AIDS patients are prone to suffer fromhypovitaminosis D because of the infection itself and the side effects of antiretroviraltherapy. Various effort have been tried to improve the immune status of HIV/AIDSpatients, one of them is by adding vitamin D. Vitamin D acts as an antiinflammatoryso that it can prevent apoptosis of CD4 T cells and increase CD4 cell count.Methods. This is a randomized control trial add on a study that aims to determinethe effect of vitamin D to increase in CD4 counts of HIV / AIDS patients who havereceived antiretroviral drugs. Subjects were HIV / AIDS patients who had receivedantiretroviral drugs. A total of 20 subjects were divided randomly into two groups;one group received vitamin D (calcitriol 0.5 mcg per day) for eight weeks, and theother group that received a placebo. Each group was measured of CD4 cell countbefore and after treatment. Results. There was a significant increase in the CD4 cellcount of the vitamin D group (p = 0.046), but not in the CD4 cell count of bothgroups (p = 0.985). The comparison of mean CD4 cell counts between groups beforetreatment was not significantly different (p = 0.057), but after treatment, it becamesignificantly different (p = 0.040). Conclusion. Vitamin D has been successful inincreasing CD4 cell count in the vitamin D group, and it is recommended to giveHIV / AIDS patients to increase CD4 cell count.